MENINGKATKAN KETERAMPILAN MEMBUAT BUNGA DARI KANTONG PLASTIK MELALUI METODE DEMONSTRASI BAGI ANAK TUNAGRAHITA RINGAN (Classroom Action Research Kelas IX SMPLB YPPC Painan) - Rama - Fajria (Universitas Negeri Padang, 2013)
The research was motivated by the problems faced by students Tunagrahita Lightweight class IX SMPLB YPPC Painan, the child's ability to make flowers out of plastic bags are still low, the child can not do independently while learning the skills to make flowers is one ditutut learning vocational skills so that children can master skills. Type of research is a classroom action research (Classroom Action Resecarh) whose team is committed to improving the quality of classroom teaching practices. The subjects were three schoolgirls mild mental retardation (SR, YL, YK) class IX SMPLB YPPC Painan. The experiment was conducted using two cycles. Cycle I conducted seven meetings and the second cycle seven meetings. Data were collected through observation, tests deeds, documents and processed qualitatively and quantitatively. Based on the results of the study indicate that: initial results (assessment) SR gain value (42.5%), YL earned value (35%) and YK earned value (30%). First cycle SR value obtained is (51.92%), YL (48.07%), and YK (44.32%). While growing up on the second cycle in which the SR gain (92.30%), YL (90.38%), and YK (88.46%). It can be concluded that the method could improve the skills demonstration to make flowers out of plastic bags for children mild mental retardation.